2012
DOI: 10.1364/ol.37.004651
|View full text |Cite
|
Sign up to set email alerts
|

Direct nanopatterning of 100 nm metal oxide periodic structures by Deep-UV immersion lithography

Abstract: Deep-UV lithography using high-efficiency phase mask has been developed to print 100 nm period grating on sol-gel based thin layer. High efficiency phase mask has been designed to produce a high-contrast interferogram (periodic fringes) under water immersion conditions for 244 nm laser. The demonstration has been applied to a new developed immersion-compatible sol-gel layer. A sol-gel photoresist prepared from zirconium alkoxides caped with methacrylic acids was developed to achieve 50 nm resolution in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Electronic properties are indeed closely linked to the nature of the metal and conditions of fabrication, which determine the structure of the final material at the atomic scale. These properties can be modified by doping with different metals, by adjusting the metal to oxygen stoichiometry or by generating an amorphous or crystal phase …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic properties are indeed closely linked to the nature of the metal and conditions of fabrication, which determine the structure of the final material at the atomic scale. These properties can be modified by doping with different metals, by adjusting the metal to oxygen stoichiometry or by generating an amorphous or crystal phase …”
mentioning
confidence: 99%
“…At the molecular scale, the patterning proceeds according to the photodecomposition of the metal precursors complexed by organic molecules. Patterning can be obtained at room temperature down to the nanoscale using direct laser writing (DLW), but usually, a thermal post‐treatment is needed to obtain an MO with suitable optical or electrical properties . For example, Yeh et al have shown that laser irradiation of a zinc oxide (ZnO) sol–gel‐based photoresist using DUV lithography can produce nanostructures .…”
mentioning
confidence: 99%
“…Zinc methacrylate precursor was chosen because metal methacrylate complexes have been proved to exhibit high sensitivity in the DUV range allowing light-induced crosslinking. Thus they were used as photosensitive building blocks to generate nanopatterning by laser direct write 17 18 . The emission wavelength of the DUV laser is 193 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The feature line‐width of photopatterned metal oxide structures is related to both photosensitivity of metal oxide precursor and the wavelength of light source. Submicro‐ or nanoscale dimensions can be achieved with the use of high photosensitive metal oxide precursors and short wavelengths light sources such as deep‐UV (DUV) (193 nm) and extreme UV (13.5 nm), making photopatterning a promising technology for fabricating micro or even nanoscale devices . Moreover, photopatterning can be applied to obtain multielement metal oxide materials by mixing photosensitive precursor in conditions that control their dispersion at the atomic scale …”
mentioning
confidence: 99%